On the nature of tense in finite control - Isac, Daniela; Richardson, Ivanna (Letras de Hoje, 2016)
This paper focuses on finite control in Persian, a language in which the embedded verb of control contexts occurs in a finite mood, more specifically in the subjunctive. Finite control poses significant challenges to classical theories of obligatory control, which exclude PRO from finite environments. Together with Landau 2013, we propose that finite control can in fact occur, under certain conditions. We show that the ambivalent nature of T in these contexts can be accounted for in a feature system which uses an interpretable/uninterpretable distinction, as well as a valued/unvalued distinction, and in which valuation and interpretability are independent from each other (Pesetsky and Torrego 2007). We propose that there are two mechanisms by which T can obtain an interpretation at LF: one is feature valuation, a process that depends on Agree and that takes place in the syntactic component, and the other one is index sharing—assigning [T] the same index as other instances of this feature with which [T] establishes a permanent link via feature checking. Apart from being able to account for the apparent conflicting behaviour of T in finite control clauses in Persian, such a system has two added benefits; (i) it allows us to derive the referential index of PRO—the null subject of finite control clauses in Persian, and (ii) it allows us to account for a surprising property of finite control clauses in Persian, namely the unavailability of overt subjects. ******************************************************************** Sobre a natureza do tempo em controle finito Resumo: Este trabalho aborda o controle finito em persa, uma língua em que o verbo encaixado de contextos de controle ocorre em modo finito, mais especificamente no subjuntivo. O controle finito apresenta desafios significativos para teorias clássicas de controle obrigatório, que excluem PRO de ambientes finitos. Seguindo Landau 2013, propomos que o controle finito possa ocorrer, sob certas condições. Mostramos que a natureza ambivalente de T nesses contextos pode ser explicada em um sistema de traços que utiliza uma distinção interpretável/não-interpretável, bem como uma distinção valorizado/não-valorizado, em que a valorização e a interpretabilidade são independentes entre si (Pesetsky e Torrego 2007). Propomos que haja dois mecanismos pelos quais T pode obter uma interpretação na FL: um é através de valorização de traços, um processo que depende de Concordância e que ocorre no componente sintático, e o outro é através de compartilhamento de índices – atribuir a [T] o mesmo índice que outras instâncias desse traço com o qual [T] estabelece um vínculo permanente através de checagem de traços. Além de poder dar conta do comportamento aparentemente conflitante de T em orações de controle finito em persa, tal sistema ainda possui dois benefícios adicionais: (i) permite a derivação do índice referencial de PRO – o sujeito nulo de orações de controle finito em persa, e (ii) permite dar conta da propriedade surpreendente de orações de controle finito em persa, a saber, a não-disponibilidade de sujeitos plenos. Palavras-chave: Controle finito; Forma lógica, T, modo finito, subjuntivo